Analysis of direction of association between radiation risk perception and relocation using a random-intercept and cross lagged panel model: The Fukushima Health Management Survey. (December 2020) - Murakami, Michio; Takebayashi, Yoshitake; Harigane, Mayumi; Mizuki, Rie; Suzuki, Yuriko; Ohira, Tetsuya; Maeda, Masaharu; Yasumura, Seiji
Abstract: In the aftermath of a nuclear disaster, a person's radiation risk perception can harm their sociopsychological health. Although there are reports of an association between radiation risk perception and relocation, the direction of this association has not been clarified yet. In this study, we used a random-intercept and cross lagged panel model (RI-CLPM) to investigate the association and its direction between radiation risk perception and the prefectural-level relocation (i.e., inside/outside of Fukushima Prefecture). We did this by using five waves of longitudinal surveys between 2011 fiscal year and 2015 fiscal year among the people affected by the Fukushima disaster in 2011. We included 90, 567 participants aged ≥15 years during the time of the disaster who responded to the questionnaire at least once. RI-CLPM was applied to examine the reciprocal relationship between radiation risk perception and locations. We used two radiation risk perception indicators (i.e., genetic effect and delayed effect) and two handling methods on missing data (i.e., listwise deletion and full information maximum likelihood estimation) as sensitive analyses. The effects of radiation risk perception on relocation were found to be negligibly small. Living inside Fukushima Prefecture reduced radiation risk perception irrespective of the difference of indicators or methods, highlighting that radiation risk perception did not dominantly govern whether people were living inside Fukushima Prefecture, but that the locations also affected radiation risk perception. This was the first study to reveal the direction of the association between radiation risk perception and relocation in the aftermath of nuclear disasters. Highlights: Directionality between radiation risk perception and relocation is ambiguous. We analyzed the bidirectionality after the Fukushima disaster in Japan. The effects of radiation risk perception on relocation are negligibly small. Living inside Fukushima Prefecture reduces radiation risk perception.